(3MGTjI ejQRLGf Ydi TQM MceI GdYjfs - (3eQRGLGf MHjH Gddgs; (3Mcje TGg , eMeO Hf eHGQc TGg Hf eMeO GdgQhj GdQhej GdMfaj, TeS GdOjf , Mcje TGg GdbRhjfj,J (B928 (3g` s
(3ChdgG (B:s
(3hEfeG bGd aGWQ PhGJ GdYbhd hde jbd aGWQ GdYbhd dFdG jJhge Cf djS ddYbhd UaGJ s
(3BNQgG (B:s
(3UQa GdMce Ydi GeJfGY GYGOI GdeYOhe s
(3MceI GdYjf dfLe GdOjf CHi GdMSf Ydi Hf eMeO GdTgjQ HOHjQGf GdcGJHi GdbRhjfi J (B675s
(3fSNI KGfjIs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B17 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B170s
Keywords: (3GdadSaI hGdefWbs